Irrigation development for rice production in the Mekong Delta, Vietnam: what's next? - Hoanh, Chu Thai; Suhardiman, Diana; Tuan, L. A. (2010)
The Vietnamese Mekong River Delta (MRD) has a total area of four million hectares for more than 18 million inhabitants in 2009 with abundant water resources (Can, 2000). Due to high seasonal variation with over 90% of rainfall and surface water concentrated during the flood season from May to November, the great potential for agriculture and aquaculture production in the MRD is only exploited if flood is controlled and irrigation in the dry season is improved. Therefore an extensive network of canals comprises of over 14,000 km of principal and primary canals, 27,000 km of secondary canals and 50,000 km of tertiary canals, and more than 20,000 km of protection dykes were built in the last 300 years. In 1985 Vietnam was still a net rice importing country, but in 1989 and 1999 it exported 1.4 and 4.6 million tons, respectively, of which the contributed more than 90%. This remarkable increase in rice production is related to the rapid growth of rice planted area in the past 35 years aided by the expansion and increased density of the irrigation and drainage system.